2007
DOI: 10.1108/17511060710837418
|View full text |Cite
|
Sign up to set email alerts
|

Customer perceived value in a cellar door visit: the impact on behavioural intentions

Abstract: PurposeThe purpose of this paper is to investigate the impact of customer perceived value on behavioural intentions in a cellar door context, and to examine the role of satisfaction as a mediator of the customer perceived value‐behavioural intentions relationship.Design/methodology/approachA multi‐dimensional measure of customer perceived value was used to determine which aspects of the cellar door experience were valued by visitors and how value dimensions impact on subsequent wine purchase intentions. Data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 55 publications
3
68
0
10
Order By: Relevance
“…Although several studies (e.g. Bajs, 2015;Gill, Byslma, & Ouschan, 2007;Oh, 1999) have examined the influence of the tourist perceived value on various aspects, lack of studies focused on the impact of different value dimensions of the PERVAL value scale. This study used a multidimensional value model as its core framework which was initially suggested by Sheth, Newman, and Gross (1991) and developed by Sweeney and Soutar (2001) into multi-dimensional PERVAL value scale.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies (e.g. Bajs, 2015;Gill, Byslma, & Ouschan, 2007;Oh, 1999) have examined the influence of the tourist perceived value on various aspects, lack of studies focused on the impact of different value dimensions of the PERVAL value scale. This study used a multidimensional value model as its core framework which was initially suggested by Sheth, Newman, and Gross (1991) and developed by Sweeney and Soutar (2001) into multi-dimensional PERVAL value scale.…”
Section: Introductionmentioning
confidence: 99%
“…Although most past research has found functional value to be signifi cant (Gill et al, 2007), in this research the economic value was found to have a high signifi cance in infl uencing customer satisfaction. However, a possible reason why economic value is highly signifi cant is that respondents feel that prices and services rendered are important in infl uencing their purchase intentions in a convenience store.…”
Section: Examining the Relationship With Customer Satisfaction And Somentioning
confidence: 53%
“…Functional value has been widely used in studies of CPV and has been found to be signifi cant in infl uencing customer satisfaction (Sweeney and Soutar, 2001;Gill et al, 2007). However, the fi ndings of the research (Tables 5 and 7) proved that functional value is insignifi cant in infl uencing customer satisfaction when related to a convenience store.…”
Section: Examining the Relationship Between Customer Satisfaction Andmentioning
confidence: 88%
See 1 more Smart Citation
“…In fact, this supported the common sense that when people scarified time and money in exchange for something and felt it totally deserved, they would be more excited to share their experience with others. A research by [72] proved both direct and indirect effects of PERVA on behavioral intentions, including word-of-mouth, through satisfaction.…”
Section: A Discussion Of the Findingsmentioning
confidence: 99%